Single-cell mRNA analysis and surface marker expression profiling of circulating immune cells in humans with alpha-gal syndrome - Choudhary, Shailesh K.; Commins, Scott P. (Frontiers in Immunology, 2025)
IntroductionAlpha-gal syndrome (AGS) is an IgE-mediated allergy to the oligosaccharide galactose-alpha-1,3-galactose (alpha-gal). Alpha-gal is found in the tissues of non-catarrhine mammals, and the characteristic delayed reactions are caused by the consumption of red meat, visceral organs, dairy, gelatin, and other products, including medications sourced from non-primate mammals. Although the syndrome is not nationally notifiable, it is estimated that 450,000 cases exist, making AGS the tenth-most common food allergy in the US. The syndrome is profoundly influenced by geographic locale, reflecting the important role of tick bites in sensitization. However, the specific immune cells, their interactions, and the downstream signaling cascades triggered by tick bites are not well understood. To address this gap, we conducted a comprehensive study to analyze the immune cells in the blood of AGS subjects compared to those of healthy controls.MethodsPeripheral blood mononuclear cell preparations were enriched for B cells from the same patient and sequentially labeled with sample tags and BD AbSeq oligo-conjugated antibodies. Sequencing libraries were prepared to targeted mRNA, antibody-oligonucleotides, and sample tags from AGS and control subjects. Multimodal analysis of both transcriptomes and surface marker expression of immune cells at the single-cell level was used to profile the immune response in AGS.ResultsSeveral clusters of cells were unique to AGS subjects, including natural killer B (NKB) cells, natural killer T (NKT) cells and most notably, a circulating mast cell progenitor population. In addition, subjects with AGS had increased expression of several genes involved in immunomodulation and type 2 immunity. Although rare, we identified and characterized alpha-gal-specific memory B cells and alpha-gal-specific IgE-secreting cells. Our findings also revealed the presence of IgE-secreting transcripts, along with other classes of immunoglobulins (Ig), in a single cell, suggesting a unique pattern of Ig gene arrangements and class switching in B cells.ConclusionsTick bites appear to induce a population of circulating mast cell progenitors and innate-like cells, such as NKT and NKB cells, that may play a critical role in sensitization to alpha-gal. Furthermore, alpha-gal-specific IgE is secreted by a heterogeneous population of B cells, including CCR6-proficient B cells and CCR6-deficient plasmablast/plasma cells.